Diversity rich solutions - Joshi, Bal Krishna; Gauchan, Devendra; Bhandari, Bharat; Jarvis, Devra I. (NAGRC, 2020)
Every household is diverse and diversity can be observed within household in terms of crops, varieties and landraces, soil type, food preferences and preparation methods, knowledge and practices related with production management of agrobiodiversity and other genetic resources. Farmers are practicing agricultural practices that promotes the use of diversity such as growing mixture of landraces, composting, fertigation. Modern agriculture focuses on developing large scale uniform technology eg use of urea, mono-genotype variety. Such system puts pressure and disturbs the ecological balance causing high risk for crop failure and genetic erosion. Any technological option with greater diversity is less risky, more sustainable and higher adaptability in agriculture. Diversity rich solution is any technology or problem associated solution that considers diversity as an option and address problems with inter and intra level diversity as well as combinations of different components. it also includes multiple technology for a single problem. Some examples are broad genetic base variety, cultivar mixtures, compost (made from different species), biopesticide (made from different species), etc. Diversity rich solution is in practice since 2014 in Nepal with the objective of conserving agrobiodiversity, promoting ecologically oriented sustainable agriculture that also enhances ecosystem services.